The Effectiveness of Rational-Emotive Behavior Group Counseling Cognitive Restructuring and Role-Playing Techniques to Reduce Bullying Behavior - Noor Khalisah; Dwi Yuwono Puji Sugiharto; Mungin Eddy Wibowo (Jurnal Bimbingan Konseling, 2024)
Bullying is a harmful behavior that intimidates and hurts other people. This research attempted to test the effectiveness of rational-emotive behavior group counseling with cognitive restructuring and role-playing techniques to reduce bullying behavior at one of the State Vocational Schools or SMK Negeri in Sampit. Experimental research with a two-factor Pre-test-Multiple post-test control design was employed in this investigation. Three groups were involved in the sampling process, each consisting of 8 tenth graders indicated to have high levels of bullying behavior. Students’ bullying behavior was measured using a bullying behavior scale based on Dupper's (2013) theory, consisting of 30 items measuring six bullying behaviors and being analyzed using the repeated mix ANOVA test. According to the findings, applying cognitive restructuring and role-playing techniques effectively reduced bullying behavior in students. It is recommended that counselors apply rational-emotive behavior group counseling with cognitive restructuring techniques and role-playing techniques to cope with students' bullying behavior.